Incorporation of Real Experiences and Artifacts As an Online Learning Intervention - Perdana, Erda Guslinar; Hikmawati, Erna; Akhmadi (LPPM POLITEKNIK LP3I BANDUNG, 2024)
Online learning has become a significant trend in recent years, but the lack of direct interaction between students and lecturers can reduce its effectiveness. This study addresses this challenge by incorporating real-world experiences—specifically two case studies, one real-world project, and simulations—alongside concrete artifacts such as software documentation, research reports, and test results. This research aims to improve the effectiveness of online learning in software verification and validation courses by incorporating real-world experiences and artifacts. A case study approach was used to test the effectiveness of this intervention by involving students from related courses. Data were collected through interviews, observations, and surveys, and analyzed qualitatively and quantitatively to understand the impact of the intervention on improving the learning experience and understanding of software verification and validation concepts. Qualitative analysis highlighted that the integration of these elements improved students' conceptual understanding and practical application skills. Quantitative results indicated a 30% increase in student engagement and a 25% improvement in understanding course material compared to prior cohorts. The findings underscore the importance of integrating real-world experiences and artifacts into online learning to promote deeper engagement, better comprehension, and more authentic learning experiences.